“Something Good Has to Come Out of the Horror”: A Qualitative Examination of Cancer Survivors' Attitudes Towards Participation in Research During the First Year of the COVID-19 Pandemic - Fox, Louis; Wylie, Harriet; Haire, Anna; Green, Saran; Kibaru, Joyce; Van Hemelrijck, Mieke (Frontiers in Public Health, 2021)
Introduction: The first year of the COVID-19 pandemic has been highly disruptive for people with cancer. Furthermore, it has been shown that accrual to cancer trials dropped substantially in 2020. Building on findings from a previous pilot survey, the present study used qualitative methods to gain insights into attitudes towards participation in research studies amongst people who have experienced cancer, in the context of the first year of the COVID-19 pandemic. Materials and Methods: We interviewed 13 participants from the UK, who were purposively sampled, including a broad sample of cancer types, and a mixture of individuals who have and have not taken part in research previously. Participants underwent semi-structured interviews (median interview duration: 47 min) and were asked open-ended questions about their attitude towards and experiences with COVID-19, and their attitude towards research participation. In addition to this, prompts were used to ask participants about concerns that were highlighted by our previous quantitative work on this topic, such as concerns about being older or having to travel to participate. Interview transcripts were analysed using a framework analysis approach. Results: Our findings suggest that cancer patient decision-making about research participation during an infectious disease pandemic may be a function of a basic cost-benefit analysis, which considers the benefit of taking part, either personally to themselves or to wider society. The benefit may then be weighed by the patient against the risk of being infected, which may be influenced by trust in the relevant clinicians/researchers; familiarity with the study location; provision of detailed information on safety protocols for infectious disease; and, in particular, the availability of safe transport to and from the study location. Discussion: Some cancer patients say that they would be less likely to participate in a research study in the middle of an infectious disease pandemic due to an increased risk to themselves. Patients' perceived risk to themselves from participating may be ameliorated via the provision of certain practical solutions that can be considered at the study protocol design stage, such as safe travel, information, and the use of staff and study sites familiar to the patient.